Exports Dynamics: Raising Developing Countries Exports Survival through Experience - Céline Carrère; Vanessa Strauss-Kahn (Fondation pour les études et recherches sur le développement international (FERDI), 2012)
This paper focuses on developing countries exports to the OECD and obtains several important results on export dynamic, linking exports experience and exports survival. It also provides insights on the role of preferential trade agreements (PTAs) in facilitating export experience and thus survival. Using product level data at the SITC 5 digit level for the 1962-2009 period, we show that prior exports experience obtained in non-OCDE markets increases survival in OECD markets. The effect of experience depreciates however rapidly with time: gaining experience for more than two years is worthless. Moreover, a break in export experience prior to entering the OECD reduces the benefit on survival. Geographic export dynamic reveals that experience is acquired in neighbor, easy to access markets before reaching more distant, richer partners and ultimately serving the OECD. PTAs among developing countries thus help exporters finding partners where to learn about their export potential. Finally, exporters may acquire experience directly within the OECD market through a process of trial and error. By facilitating this process, PTAs between developing countries and the OECD help boosting survival in the long run.
Keywords: C41; F10; F14; 330